Aksi Lomba Beach Cleaning pada Program Conservation Goes to School di Dermaga Tawun, Sekotong Barat - Wulandari, Witri; Susianti, Lena; Umami, Riza; Abidin, Zaenal; Setyono, Bagus Dwi Hari; Diniariwisan, Damai; Affandi, Rangga Idris; Sumsanto, Muhammad; Asri, Yuliana; Marzuki, Muhammad (Jurnal Gema Ngabdi, 2024)
Community service activities carried out by the Deep Blue Sea Foundation and Mataram University KKN-MBKM students in Tawun Hamlet, West Sekotong Village, got a positive response from the local community. This event involved various parties, such as the Lombok Marine Aquaculture Center (BPBL) and security forces, which showed strong cross-sector collaboration. This activity aims to increase environmental awareness by involving 78 students from seven elementary schools through various activities, such as beach cleaning and eco-brick making. Beach clean-ups were the focus of the activity, with students divided into groups to collect rubbish from the coastal environment. As a result, 116 kg of waste was collected, consisting of 55 kg of organic waste and 61 kg of inorganic waste. The rubbish is then taken to the available waste management facilities. Students also play an active role in mentoring and facilitating activities, showing positive synergy between universities and the community. This activity is expected to have a positive impact on environmental cleanliness and public awareness of the importance of environmentally sound behavior. Therefore, similar activities are recommended to be integrated into the school curriculum and replicated in other regions to encourage changes in people’s behavior towards a sustainable lifestyle.